2003
DOI: 10.1080/09637480120092143
|View full text |Cite
|
Sign up to set email alerts
|

Total beverage consumption and beverage choices among children and adolescents

Abstract: Patterns of beverage consumption among children and adolescents are related to age, race, and gender. The relationship between body mass index (BMI) and beverage consumption is unclear. In this paper, the total amount and the types of beverages consumed were analyzed according to age, race, and gender. Multivariate regression models were estimated for consumption of milk, juices, fruit drinks/ades, and carbonated soft drinks. Descriptive and multivariate regression analysis of children aged 6-19 from the US De… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
146
2
8

Year Published

2004
2004
2014
2014

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 194 publications
(171 citation statements)
references
References 3 publications
14
146
2
8
Order By: Relevance
“…73 Whether beverage consumption refers to uid milk, to fruit drinks, to citrus and non-citrus juices or to carbonated so drinks, the trend is the same: boys of all ages drink more than girls do. 71 With respect to differences by age, some studies have pointed out that the consumption of so drinks increases from childhood to adolescence. Grimm et al (2004) 72 reported an increase of so drink consumption in children from 8 to 13 years old.…”
Section: Consumption and Preference Patternsmentioning
confidence: 99%
See 1 more Smart Citation
“…73 Whether beverage consumption refers to uid milk, to fruit drinks, to citrus and non-citrus juices or to carbonated so drinks, the trend is the same: boys of all ages drink more than girls do. 71 With respect to differences by age, some studies have pointed out that the consumption of so drinks increases from childhood to adolescence. Grimm et al (2004) 72 reported an increase of so drink consumption in children from 8 to 13 years old.…”
Section: Consumption and Preference Patternsmentioning
confidence: 99%
“…72 In addition, the parents are the ones deciding what foods and drinks should be available and accessible at home. 71 …”
Section: Environmental Factorsmentioning
confidence: 99%
“…36,47 Neither of 2 nationally representative, cross-sectional studies found a relationship between fruit juice consumption and reported BMI. 48,49 One casecontrol study and 3 other cross-sectional studies found a positive association between fruit juice intake and a measure of adiposity. 29,39,50,51 In 2 studies of related cohorts, only large amounts of juice (Ն12 fl oz/day) were associated with increased obesity.…”
Section: Fruits and Vegetablesmentioning
confidence: 99%
“…Although some studies have shown an association between 100 % FJ consumption and weight (4)(5)(6)(7) , the majority have not (8)(9)(10)(11)(12)(13)(14) . A systematic review published in 2008 showed no consistent association between consumption of 100 % FJ and overweight/obesity in children or adolescents (14) .…”
mentioning
confidence: 99%